Surgical treatment of kidney tuberculosis: a comparative analysis of open and laparoscopic approaches - D. P. Kholtobin (Вестник урологии, 2020)
Introduction. Tuberculosis remains a global problem of our time. Kidney tuberculosis, especially complicated by tuberculosis of the urinary tract, becomes a surgical disease if it diagnosed late or the therapy was not optimal.Materials and methods. 93 patients with urogenital tuberculosis (UGTB) was included in this study who were admitted to the Novosibirsk Scientific and Research Institute of Tuberculosis consecutively. All of them underwent surgical intervention on the kidney. 51 patients underwent open surgery, and 42 patients underwent laparoscopic surgery. The results of treatment and the incidence of complications in both groups were analyzed and compared.Results. The age of the patients ranged from 23 to 75 years, averaging 50.9 ± 6.7 years; there were 45 men and 48 women. Tuberculosis of the left kidney was diagnosed in 41 patients, on the right - in 52 patients. The indication for nephrectomy was polycavernous tuberculosis of the kidney with no function in 74 cases, while in 11 cases polycavernous tuberculosis was complicated by stage 4 bladder tuberculosis. In 9 patients, nephrectomy was performed with cystectomy simultaneously. In 2 patients with severe renal dysfunction, cystectomy for microcystis was not performed, preferring laparoscopic nephrectomy with heterotopic urine diversion. In the group of patients operated on with an open approach, complications developed in 14 patients (27.4%), in the group of laparoscopic operations - in 5 (11.9%). The laparoscopic approach made it possible to activate the patients much earlier: after 2.4 hours, while in the openaccess group - after 38.7 hours.Conclusion. Due to the peculiarities of the pathogenesis of UGBT, it is accompanied by the local development of gross deforming scars, which significantly complicates the implementation of the surgical procedure - both open and laparoscopic access. Nevertheless, modern technology allows to perform the entire spectrum of operations laparoscopically to UGTB, and the complication rate is 2.3 times lower than in open operations. Early activation of the patient, less need for analgesics are also positive factors of minimally invasive surgery for UGTB.